Coral Plant (Jatropha multifida L) for Postpartum Perineal Wound Care: A Literature Review - Fera, Fitria Candra; Marsum, Marsum; Rahayu, Sri (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2025)
Postpartum maternal pain increases with injuries to the birth canal. Some cases of postpartum infections are caused by improper perineal wound care, which causes bacterial growth. If the perineal wound is not treated with proper care, it can lead to infection and even death in some cases. Traditional plant as nonpharmacological therapy such as Jatropha multifida L. could be one of alternative therapy for wound healing. The purpose of this study was to examine the potential of secondary metabolites found in the Jatropha multifida L. plant as antibacterial and anti-inflammatory as an effort to heal perineal wounds in postpartum mothers. This study used the PRISMA (Preferred Reporting Items for Systematic Review and Meta Analysis) method. Five literatures was obtained from several literature search engines, namely Science Direct, Google Scholar, PubMed, ResearchGate, and ProQuest. The keywords used in the search were